ASSESSMENT OF KNOWLEDGE AMONG SURGICAL NURSES REGARDING SURGICAL TIME OUT PROTOCOLS IN THE OPERATING ROOM AT TERTIARY HOSPITAL RAWALPINDI - ULLAH , N; RAFIULLAH, .; IRFAN, M; KAUSAR, H; RAJPER , A; KUMAR, V; MAGSI, S (Biological and Clinical Sciences Research Journal, 2024)
Surgical Time Out protocols are pivotal for ensuring patient safety in operating rooms (ORs), designed to prevent surgical errors such as wrong-patient surgery and retained surgical instruments. Despite established protocols, adherence varies, with potentially fatal outcomes. Aim: The study aims to assess the knowledge and implementation of Surgical Time Out protocols among surgical nurses at a Tertiary Care Hospital in Rawalpindi, determining the impact on patient safety and surgical outcomes. Methods: We conducted a descriptive cross-sectional study involving 150 OR nurses selected through convenience sampling. A validated questionnaire was employed to collect data on the nurses' knowledge and application of Time Out protocols. Results: Results showed that 68% of nurses had adequate knowledge regarding Time Out protocols, recognizing their essential role in patient safety. Nevertheless, 32% had insufficient knowledge, which could compromise surgical safety. Conclusion: The study concludes that while a majority of nurses understand the importance of Surgical Time Out protocols, there is a significant portion who require further training. It emphasizes the necessity of regular, structured training programs to enhance adherence to Time Out protocols, thereby improving patient safety and reducing preventable surgical complications.